Professional self-assessment of future health basics teachers as professionally important quality - Radchenko, A.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to theoretically substantiate and experimentally test professional self-assessment of future health basics teachers as professionally important quality. Material: 152 students participated in experiment. Results: assessment of images “I am real”, “I am student” and I am future professional” is rather high in most of students. The strength of these three images was assessed also approximately equally. But portion of average marks in indicator of image strength is much higher than in indicator of mark. Activity of three images differs a little and has significant quantity of average and high marks. Analysis of three main images’ wholeness witnesses that students’ self assessment is rather holistic. With it image “I am future professional” is formed on the base of image “I am student”. Dynamic of images’ self assessment witnesses that increasing of assessment and respect to image “I am future professional” depend on year of studying. Besides, assessment of strength and activity of this image also increases. Conclusions: in the process of studying students are oriented on professional formation as well as on formation of professionally important qualities, revelation of potential for self realization in the future. It was found that responsible attitude to professional functioning, future relations with children depend on self-assessment of formation.